Dominant role of ammonia-oxidizing bacteria in nitrification due to ammonia accumulation in sediments of Danjiangkou reservoir, China - Dang, Chenyuan; Liu, Wen; Lin, Yaxuan; Zheng, Maosheng; Jiang, Huan; Qian Chen; Ni, Jinren (Applied Microbiology and Biotechnology, 2018)
Surface sediments are the inner source of contaminations in aquatic systems and usually maintain aerobic conditions. As the key participators of nitrification process, little is known about the activities and contributions of ammonia-oxidizing archaea (AOA) and bacteria (AOB) in the surface sediments. In this study, we determined the net and potential nitrification rates and used 1-octyne as an AOB specific inhibitor to detect the contributions of AOA and AOB to nitrification in surface sediments of Danjiangkou reservoir, which is the water source area of the middle route of South-to-North Water Diversion Project in China. Quantitative PCR and Illumina high-throughput sequencing were used to evaluate the abundance and diversity of the amoA gene. The net and potential nitrification rates ranged from 0.42 to 1.93 and 2.06 to 8.79 mg N kg−1 dry sediments d−1, respectively. AOB dominated in both net and potential nitrification, whose contribution accounted for 52.7–78.6% and 59.9–88.1%, respectively. The cell-specific ammonia oxidation rate calculation also revealed the cell-specific rates of AOB were higher than that of AOA. The Spearman's rank correlation analysis suggested that ammonia accumulation led to the AOB predominant role in net nitrification activity, and AOB abundance played the key role in potential nitrification activity. Furthermore, phylogenetic analysis suggested AOB were predominantly characterized by the Nitrosospira cluster, while AOA by the Nitrososphaera and Nitrososphaera sister clusters. This study will help us to better understand the contributions and characteristics of AOA and AOB in aquatic sediments and provide improved strategies for nitrogen control in large reservoirs.